Sorrel for sale - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Samuel Taryanouba, of the Groupement de Producteurs de Karkandji (GPK, BP 97, Koumra, Chad) says the group 'comprises twenty farmers of sorrel (oseille de Guinée in French, karkandji in Arabic, bisap in Wolof and agria in Jamaica). We have agreed...